2020
DOI: 10.21203/rs.3.rs-18527/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Angiotensin AT1 and AT2 receptor heteromer expression in the hemilesioned rat model of Parkinson’s disease that increases with levodopa-induced dyskinesia

Abstract: Background/Aims: The renin-angiotensin system (RAS) is altered in Parkinson’s disease (PD), a disease due to substantia nigra neurodegeneration and whose dopamine-replacement therapy, using the precursor levodopa, leads to dyskinesias as the main side effect. Angiotensin AT1 and AT2 receptors, mainly known for their role in regulating water homeostasis and blood pressure and able to form heterodimers (AT1/2Hets), are present in the central nervous system. We assessed the functionality and expression of AT1/2He… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In addition, MasR is key for microglia-driven development of the retinal vasculature [87]. The results presented here and those related to expression of AT 1 R-AT 2 R heteromers in striatal cells [42] suggest that MasR-related therapies to delay progression of PD should consider RAS components in microglia, with the ultimate goal of attenuating inflammation or skewing microglia toward the M2 neuroprotective phenotype [64]. RAS is well positioned to be targeted to polarization of microglia activated upon neuroinflammation [82].…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…In addition, MasR is key for microglia-driven development of the retinal vasculature [87]. The results presented here and those related to expression of AT 1 R-AT 2 R heteromers in striatal cells [42] suggest that MasR-related therapies to delay progression of PD should consider RAS components in microglia, with the ultimate goal of attenuating inflammation or skewing microglia toward the M2 neuroprotective phenotype [64]. RAS is well positioned to be targeted to polarization of microglia activated upon neuroinflammation [82].…”
Section: Discussionsupporting
confidence: 56%
“…At the beginning of the twenty-first century, research on GPCRs uncovered a novel property resulting from the the nigra and the striatum was followed by the identification of complexes formed by AT 1 R and AT 2 R [39,42]. In this paper, we showed that the Mas receptor forms heteroreceptor complexes with AT 1 R and AT 2 R and that such complexes are relevant for better understanding the role of RAS in neuroinflammation.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…All receptors related to both Ang and Ang1-7 are expressed in microglia and contribute to the regulation of cell activation. There is interest in knowing whether the neurologic alterations observed in some COVID-19 patients are somehow mediated by the RAS system expressed in neurons and/or microglia (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). However, our focus in this review is RAS in macrophages, which release IL-6 when activated and also express RAS components.…”
Section: Ras Gpcrs the Blind Point In Sars Researchmentioning
confidence: 99%